The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1677/joe.0.1210409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term starvation on reproductive hormone gene expression, secretion and receptor levels in male rats

Abstract: The effects of 4-6 days of food deprivation on the pituitary-testicular function of adult male rats were studied. Fasting decreased body weights on average by 23% (P less than 0.01) and those of seminal vesicles by 55% (P less than 0.01) in 4 days. No consistent changes were found in testicular and ventral prostate weights. The pituitary levels of gonadotrophin-releasing hormone (GnRH) receptors decreased by 50% (P less than 0.01). Serum and pituitary levels of LH, FSH and prolactin decreased by 25-50% (P less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 30 publications
(39 reference statements)
3
41
1
Order By: Relevance
“…We also showed that starvation induced decreases in mRNAs encoding the LHβ-, FSHβ-and common α-subunit precursor molecules in the Japanese quail. In the rat, it was reported that starvation had a suppressive effect on the levels of FSHβ and common α mRNAs and no effect on the level of LHβ mRNA in the pituitary gland (Bergendahl et al, 1989 andBergendahl and Huhtaniemi, 1993). In the sheep, it was reported that long-term food restriction had no effect on the levels of gonadotropin subunit mRNA while it decreased levels of plasma gonadotropins (Thomas et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also showed that starvation induced decreases in mRNAs encoding the LHβ-, FSHβ-and common α-subunit precursor molecules in the Japanese quail. In the rat, it was reported that starvation had a suppressive effect on the levels of FSHβ and common α mRNAs and no effect on the level of LHβ mRNA in the pituitary gland (Bergendahl et al, 1989 andBergendahl and Huhtaniemi, 1993). In the sheep, it was reported that long-term food restriction had no effect on the levels of gonadotropin subunit mRNA while it decreased levels of plasma gonadotropins (Thomas et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…A series of papers with such approach has been published for the rat (Bergendahl et al ., 1989 andBergendahl and Huhtaniemi, 1993), with a similar paper also on the sheep (Thomas et al ., 1990).…”
Section: Introductionmentioning
confidence: 99%
“…CR-induced suppression of the pulsatile release of GnRH from the hypothalamus is considered to be the central mechanism by which this reproductive perturbation occurs (Veldhuis et al, 1993;Cameron et al, 1991). It has been shown that GnRH receptor content (which is controlled by GnRH levels in the hypophyseal portal system) in the pituitary is sensitive to CR and fasting (Bergendahl et al, 1989;Greuenwald and Matusmoto, 1993). The resultant effects of short-term fasting, i.e.…”
Section: Ghrelin and Growth Hormonementioning
confidence: 99%
“…Reduced food intake is known to be associated with reproductive dysfunction in humans (1,2), and rats (3)(4)(5). Several kinds of endogenous sugar acids found in rat blood have been reported to be involved in control of food intake (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports (3)(4)(5) that fasting impairs the pulsatile secretion of LH and that the specific opioid antagonist, naloxone or naltrexone, reverses this impairment (12,13). Therefore, EOPs may be involved in the 2-B4O-induced decrement in LH secretion.…”
Section: Introductionmentioning
confidence: 99%